Quantificando a fragilidade estatal: o caso do G7+ - Vanderlei, Larissa Pinz (2024)
With the growing importance of the issue of state fragility in the development agenda, the need for quantitative methods to identify countries in this condition has been driven forward, in order to increase the effectiveness of aid. It is possible to observe a convergence between the Fragile States Agenda and the practice of quantifying development since the 2000s. This research highlights the role of the OECD and the World Bank in creating the concept and producing knowledge of "Fragile States". I argue that the entry of new non-Western actors into this agenda is beginning to challenge this dynamic, bringing different perspectives to the debate on development. Thus, the study analyzes the case of the g7+, a group that calls itself fragile states, and its self-assessment tools, arguing that the appropriation of the term by the g7+, while questioning, also strengthens the role of numbers in the formulation of development policies, subtly altering the power relations present in this Agenda